High-Precision Fast-Spiking Basket Cell Discharges during Complex Events in the Human Neocortex - Szegedi, Viktor; Molnár, Gábor; Paizs, Melinda; Csakvari, Eszter; Barzó, Pál; Tamás, Gábor; Lamsa, Karri (eNeuro, 2017)
In the human neocortex, solitary action potentials in some layer 2–3 pyramidal cells (PCs) trigger brief episodes of network activity known as complex events through strong excitatory synapses that specifically innervate GABAergic interneurons. Yet, how these “master PCs” configure the local network activity is not well understood. We report that single spikes in the PCs, studied here in synaptically connected cell pairs in frontal or temporal neocortical areas of both males and females, elicit firing of fast-spiking basket cells (FSBCs) with a short delay (on average 2.7 ms). The FSBC discharge is triggered by 13 mV (on average) monosynaptic EPSPs, and the action potential is time locked to the master PC spike with high temporal precision, showing little jitter in delay. In the complex events, the FSBC discharge occurs in the beginning of the activity episode, forming the first wave of the complex event activity. Firing of FSBCs generates GABAergic IPSCs with fast kinetics in layer 2–3 PCs, and similar IPSCs regularly occur time locked to master PC spikes in the beginning of the complex events with high probability and short (median 4.1 ms) delay with little jitter. In comparison, discharge of nonfast spiking interneurons (non-FSINs) investigated here appears inconsistently in the complex events and shows low probability. Thus, firing of layer 2–3 FSBCs with high temporal fidelity characterizes early phase of the complex events in the human neocortex.